Crystal Structure of an Intramolecular Mesaconyl-Coenzyme A Transferase From the 3-Hydroxypropionic Acid Cycle of Roseiflexus castenholzii - Min, Zhenzhen; Zhang, Xin; Wu, Wenping; Xin, Yueyong; Liu, Menghua; Wang, Kangle; Zhang, Xingwei; He, Yun; Fan, Chengpeng; Wang, Zhiguo; Xu, Xiaoling (Frontiers in Microbiology, 2022)
Coenzyme A (CoA) transferases catalyze reversible transfer of CoA groups from CoA-thioesters to free acids, playing important roles in the metabolism of carboxylic acids in all organisms. An intramolecular CoA transferase, Mesaconyl-CoA C1-C4 CoA transferase (MCT) was identified in the autotrophic CO2 fixation pathway, 3-hydroxypropionic acid cycle of filamentous anoxygenic phototrophs (FAPs). Different from the well-known CoA transferases that catalyze CoA transfer between two distinct substrates, MCT specifically catalyzes the reversible transformation of mesaconyl-C1-CoA to mesaconyl-C4-CoA, a key reaction intermediate for carbon fixation. However, the molecular mechanism of MCT in employing one substrate is enigmatic. Here we determined the crystal structure of MCT from a chlorosome-less FAP Roseiflexus castenholzii at 2.5 Å resolution, and characterized the catalytic mechanisms through structural analyses and molecular dynamic simulations. The structure of R. castenholzii MCT consists of a Rossmann fold larger domain and a small domain that are connected by two linkers. Two MCT subunits are cross interlocked at the linker regions to form a functional dimer in solution, in which the substrate binding pockets are located at the interface of the Rossmann fold larger domain from one subunit and the small domain from the other subunit. In the simulated binding structures, both the substrate mesaconyl-C1-CoA and product mesaconyl-C4-CoA form extensive electrostatic and hydrogen bonding interactions with MCT. But some differences exist in the binding mode of these two CoA analogs, Arg314’ from the second subunit of the dimer presenting dramatic conformational changes in binding with mesaconyl-C4-CoA. Together with Arg47 and one water molecule, a strictly conserved residue Asp165 are essential for catalyzing the reversible intramolecular CoA transfer reaction, through the electrostatic and hydrogen bonding interactions with the mesaconic tail of both the substrate and product. This study revealed a previously unrecognized mechanism for the uncommon intramolecular CoA transfer reaction, which will not only broaden the knowledge on the catalytic mechanisms of CoA transferases, but also contribute to enzyme engineering or biosynthetic applications of the 3-HP cycle for synthesis of fine chemicals and important metabolites.